2015
DOI: 10.1007/s11284-015-1301-3
|View full text |Cite
|
Sign up to set email alerts
|

Links in the functional diversity between soil microorganisms and plant communities during natural succession in coal mine spoil heaps

Abstract: The successful establishment of vegetation, soil development and biogeochemical cycling during the restoration process of mine tailings requires a diverse and metabolically active microbial communities. The objective of this study was to test whether there is any link between the functional groups of both the dominant plant species and soil microbial communities on unreclaimed coal mine spoil heaps of different age located in the Silesian Upland (Poland). At each sampling site the dominant plant species were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…The evenness values also suggest that the proportion of the physiologically distinct (with respect to carbon utilisation) species in the community are similar across soils. In a study by Markowicz et al 17 , no differences were observed in the functional diversity (as determined by carbon utilisation profiles) of plant-associated microbial communities in coal mining soil stockpiles -of different ages of natural reclamation. Summarily, these observations hint at functional redundancy within the microbial communities for metabolising carbon.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The evenness values also suggest that the proportion of the physiologically distinct (with respect to carbon utilisation) species in the community are similar across soils. In a study by Markowicz et al 17 , no differences were observed in the functional diversity (as determined by carbon utilisation profiles) of plant-associated microbial communities in coal mining soil stockpiles -of different ages of natural reclamation. Summarily, these observations hint at functional redundancy within the microbial communities for metabolising carbon.…”
Section: Discussionmentioning
confidence: 90%
“…Similar to the study of Li et al 45 on post-coal reclamation and unmined soils in China, several dominant and rare bacterial phylotypes, including Proteobacteria, Actinobacteria, Chloroflexi, Acidobacteria, Planctomyces and Verrucomicrobia were observed across reclamation and reference soils. Some species of these phyla contribute to the diverse microbial functions and process in the soil ecosystems, including processes that are critical to soil ecosystem sustainability 17,48,49 . The relatively abundant phyla included underexplored phyla divisions such as WPS-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent studies have investigated links between particular groups of organisms, and general relationships between diversity and processes have been found. However, studies either detail microbial diversity across general vegetation, land use or habitat classes (Chen et al, 2015;Flores-Rentería, Rincón, Valladares, & Yuste, 2016;Kaiser et al, 2016;Paula et al, 2014), correlate the general processes governed by microbes (such as soil respiration, microbial biomass or microbial enzyme activities) with detailed surveys of plant communities (Purahong et al, 2016;Strecker, González Macé, Scheu, & Eisenhauer, 2016) or infer microbial diversity indirectly from the physiological profiling of soil samples ("functional diversity"), rather than determining taxonomic diversity directly via genetic analysis (Araya, Bartelheimer, Valle, Crujeiras, & García-Baquero, 2017;Klimek, Chodak, Jaźwa, & Niklińska, 2016;Klimek et al, 2015;Markowicz, Woźniak, Borymski, Piotrowska-Seget, & Chmura, 2015;Mureva & Ward, 2017). The responses of microbial functional and taxonomic diversities to changes in plant productivity are not directly comparable (Zhang, Johnston, Barberán, Ren, & Lü, 2017) and likely reflect the operation of different processes.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the exploitation of mineral deposits and the storage of waste coming from extraction and processing works, a lot of anthropogenic forms were created, such as spoil heaps or sedimentation pools. The spoil heaps are distinguished by specific harsh conditions (Bradshaw, 1993), such as: lack of water, high temperature, sometimes high salinity, low nutrient availability, small amount or lack of organic carbon (organic matter), small amount of nitrogen and macroelements (P, Mg, K) [Bradshaw, 2000;Rostański, Woźniak 2007;Woźniak et al, 2003, Woźniak, 2010Markowicz et al, 2015]. Since in many places the process of vegetation development is very slow, such heaps are susceptible to water or wind erosion [Bradshaw, developed vegetation is dominated by grasses.…”
Section: Introductionmentioning
confidence: 99%